EFEITOS DE MODOS DE APLICAÃ‡ÃƒO, DOSES E FONTES DE POTÃSSIO NA PRODUÃ‡ÃƒO DA SOJA - Rosolem, Ciro A.; Nakagawa, JoÃ£o; Machado, JosÃ© Ricardo; Yamada, T. (REVISTA DE AGRICULTURA, 2020)
EFEITOS DE MODOS DE APLICAÃ‡ÃƒO, DOSES E FONTES DE POTÃSSIO NA PRODUÃ‡ÃƒO DA SOJA